2021
DOI: 10.1021/jacs.1c04919
|View full text |Cite
|
Sign up to set email alerts
|

The Oxo-Wall Remains Intact: A Tetrahedrally Distorted Co(IV)–Oxo Complex

Abstract: In this paper, we report the preparation, spectroscopic and theoretical characterization, and reactivity studies of a Co(IV)−oxo complex bearing an N4-macrocyclic coligand, 12-TBC (12-TBC = 1,4,7,10-tetrabenzyl-1,4,7,10-tetraazacyclododecane). On the basis of the ligand and the structure of the Co(II) precursor, [Co II (12-TBC)(CF 3 SO 3 ) 2 ], one would assume that this species corresponds to a tetragonal Co(IV)−oxo complex, but the spectroscopic data do not support this notion. Co K-edge XAS data show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 87 publications
2
18
0
Order By: Relevance
“…The discoveries of high-valent metal-oxo species as key intermediates in a variety of enzymatic transformations have inspired numerous biomimetic and bio-inspired efforts trying to understand the structural and spectroscopic properties and substrate oxidation reactivities of these species. , While a large inventory of synthetic M­(IV)O complexes for first-row early and middle transition metal elements (Cr, Mn, and Fe) have become available, high-valent metal-oxo complexes for late transition metals (Co, Ni, and Cu) are rare, as predicted by the classic bonding theory. , Alternatively, diverging the synthetic effort from the metal-oxo territory to develop non-oxo-metal complexes of late transition metals appears to be an effective strategy that provides more flexibility to study the rich chemistry of their high-valent derivatives . For example, a number of groups, including us, have described oxo- and non-oxo-Co­(IV) species capable of oxidizing sp 3 C–H bonds. For Ni and Cu, the +3 oxidation state is typically considered as “high valent”. A number of Ni­(III)- and Cu­(III)-hydroxo, carboxylate, and halide complexes are strong oxidants and hydrogen atom transfer (HAT) reagents; however, examples of these two metals having formal +4 oxidation states are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The discoveries of high-valent metal-oxo species as key intermediates in a variety of enzymatic transformations have inspired numerous biomimetic and bio-inspired efforts trying to understand the structural and spectroscopic properties and substrate oxidation reactivities of these species. , While a large inventory of synthetic M­(IV)O complexes for first-row early and middle transition metal elements (Cr, Mn, and Fe) have become available, high-valent metal-oxo complexes for late transition metals (Co, Ni, and Cu) are rare, as predicted by the classic bonding theory. , Alternatively, diverging the synthetic effort from the metal-oxo territory to develop non-oxo-metal complexes of late transition metals appears to be an effective strategy that provides more flexibility to study the rich chemistry of their high-valent derivatives . For example, a number of groups, including us, have described oxo- and non-oxo-Co­(IV) species capable of oxidizing sp 3 C–H bonds. For Ni and Cu, the +3 oxidation state is typically considered as “high valent”. A number of Ni­(III)- and Cu­(III)-hydroxo, carboxylate, and halide complexes are strong oxidants and hydrogen atom transfer (HAT) reagents; however, examples of these two metals having formal +4 oxidation states are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism shown in Scheme A invokes a key Co IV -oxo intermediate. Such high-valent Co complexes are quite rare although they have been invoked as reactive intermediates. ,,,, While there are two examples of spectroscopically characterized terminal Co IV -oxo species, they do not engage in the activation of aliphatic C–H bonds. , Therefore, we set out to observe any transient Co IV complex in order to support the proposed agency of 4 ox . We first monitored the addition of FcBF 4 to solutions of 4 by UV–vis spectroscopy at temperatures lower than −80 °C in the hopes of slowing down the reaction enough to observe 4 ox .…”
Section: Results and Discussionmentioning
confidence: 93%
“…32,39,40,53,54 While there are two examples of spectroscopically characterized terminal Co IV -oxo species, they do not engage in the activation of aliphatic C−H bonds. 40,42 Therefore, we set out to observe any transient Co IV complex in order to support the proposed agency of 4 ox . We first monitored the addition of FcBF C−H activation reactions mediated by transition metal-oxo and hydroxide complexes frequently have large deuterium kinetic isotope effects (KIEs), especially at low temperatures.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that formally, Co–O complex should be best described as a Co­(III)-oxyl tautomer by calculations. Besides, a Lewis acid or the hydrogen bond could stabilize a metal–oxo unit by reducing the electron density of the terminal oxo donor and allow for the characterization of a Co­(IV)–oxo species. These studies shed light on the potential to develop chiral multidentate ligand-based Co–O complexes for asymmetric epoxidation.…”
Section: Introductionmentioning
confidence: 99%